When Experimental Practice Comes First - Ghelfi, Andrea; Papadopoulos, Dimitris; Pellizzoni, Luigi; Raffaetà, Roberta (Tecnoscienza – Italian Journal of Science & Technology Studies, 2021)
This article hosts a vivid discussion on Papadopoulos’ book Experimental Practice. Technoscience, Alterontologies and More-Than-Social Movements (Duke University Press, 2018). This is a speculative and politically engaged book. It crosses the boundaries of social theory, science and technology studies, feminist theory and autonomist thought. The following contributions explore and critically discuss an essential topic of the book: the role of movements and everyday practices in transforming eco-societies from below. Andrea Ghelfi situates the book in an historical contingency in which social transformation is primarily driven by material, ontological transformation. Luigi Pellizzoni offers an analysis of the ambivalences of experimentalism in a context marked by neoliberal governmentality. Roberta Raffaetà brings attention to three interrelated themes: practice, theory and the role of institutional power. Finally, Dimitris Papadopoulos’ response focuses on the complicate relation between practice and politics in more-than-social movements.